Timing and Dose of Upper Limb Motor Intervention After Stroke: A Systematic Review. Issue 11 (4th October 2021) - Hayward, Kathryn S.; Kramer, Sharon F.; Dalton, Emily J.; Hughes, Gemma R.; Brodtmann, Amy; Churilov, Leonid; Cloud, Geoffrey; Corbett, Dale; Jolliffe, Laura; Kaffenberger, Tina; Rethnam, Venesha; Thijs, Vincent; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : This systematic review aimed to investigate timing, dose, and efficacy of upper limb intervention during the first 6 months poststroke. Three online databases were searched up to July 2020. Titles/abstracts/full-text were reviewed independently by 2 authors. Randomized and nonrandomized studies that enrolled people within the first 6 months poststroke, aimed to improve upper limb recovery, and completed preintervention and postintervention assessments were included. Risk of bias was assessed using Cochrane reporting tools. Studies were examined by timing (recovery epoch), dose, and intervention type. Two hundred and sixty-one studies were included, representing 228 (n=9704 participants) unique data sets. The number of studies completed increased from one (n=37 participants) between 1980 and 1984 to 91 (n=4417 participants) between 2015 and 2019. Timing of intervention start has not changed (median 38 days, interquartile range [IQR], 22–66) and study sample size remains small (median n=30, IQR 20–48). Most studies were rated high risk of bias (62%). Study participants were enrolled at different recovery epochs: 1 hyperacute (<24 hours), 13 acute (1–7 days), 176 early subacute (8–90 days), 34 late subacute (91–180 days), and 4 were unable to be classified to an epoch. For both the intervention and control groups, the median dose was 45 (IQR, 600–1430) min/session, 1 (IQR, 1–1) session/d, 5 (IQR, 5–5) d/wk for 4 (IQR, 3–5) weeks. The most common interventions tested were electromechanical (n=55 studies), electrical stimulation (n=38 studies), and constraint-induced movement (n=28 studies) therapies. Despite a large and growing body of research, intervention dose and sample size of included studies were often too small to detect clinically important effects. Furthermore, interventions remain focused on subacute stroke recovery with little change in recent decades. A united research agenda that establishes a clear biological understanding of timing, dose, and intervention type is needed to progress stroke recovery research. Prospective Register of Systematic Reviews ID: CRD42018019367/CRD42018111629.